Estudo de coorte retrospectiva para avaliação da efetividade do Ácido Acetilsalicílico no prognóstico e evolução de pacientes com COVID-19 em hospital da região metropolitana de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Thrombosis and disseminated intravascular coagulation are among the most serious complications of COVID-19. There is evidence that prophylactic dose acetylsalicylic acid therapy can reduce the risk of thrombosis in patients with COVID-19, given that this drug is effective as an antiplatelet agent in cardiovascular and thromboembolic diseases. In this scenario, the main objective of the present study was to assess whether the routine and previous use of acetylsalicylic acid could reduce mortality in patients hospitalized for complications with COVID-19. In this way, a retrospective study was developed of all people hospitalized at the Municipal Hospital of Aparecida (Goiânia, State of Goiás), between October 1, 2020 and April 9, 2021 with confirmed infections by COVID-19. Inclusion criteria were patients over 18 years of age, confirmed infection by COVID-19, with follow-up until the 28th day of hospitalization, discharge or death. The control group consisted of patients hospitalized for COVID- 19, not exposed to acetylsalicylic acid medication. To capture the clinical outcomes of interest, the main primary outcome analyzed was death. The secondary outcomes analyzed were the need for oxygen therapy, mechanical ventilation, admission to the intensive care unit and hemodialysis. The results of this study revealed that 40.12% of people hospitalized with COVID-19 met the inclusion criteria. A significantly lower number of deaths were observed among those inpatients with COVID-19 who were already routinely using aspirin and those in patients who were not using the drug. In addition, the results demonstrated that continued use of acetylsalicylic acid decreased the need for oxygen therapy, hemodialysis, intensive care unit admission, and mechanical ventilation in patients with COVID-19. However, there is a need to develop more clinical and observational studies that prove the effect of acetylsalicylic acid in the prevention and treatment of COVID-19.
Keywords: Antiagregante plaquetário; Aspirina; Coronavírus - Trombose; Aspirin; Thrombosis - Coronavirus; Antiplatelet agent; COVID-19 - Acetilsalicílico; CIENCIAS DA SAUDE